Pengaruh budaya organisasi dan pengalaman kerja terhadap kompetensi dan kinerja pegawai di Kantor Pertanahan Kabupaten Musi Rawas - Pratami, Eggi Indriani (Nur Science Institute, 2024)
This study aims to analyze the influence of organizational culture and work experience on the competence and performance of employees at the Land Office of Musi Rawas Regency. The research sample consisted of 31 respondents, with data collected through questionnaires. Data analysis was conducted using quantitative methods, employing both simple and multiple linear regression techniques. The results of the study show that organizational culture has a significant impact on employee performance. Work experience also significantly influences employee performance. Additionally, the study found that organizational culture and work experience partially affect employee competence. Simultaneously, organizational culture and work experience significantly impact both employee performance and competence. The implications of this research emphasize the importance of developing organizational culture and enhancing work experience as efforts to improve employee competence and performance in the workplace.